2006
DOI: 10.3318/bioe.2006.106.3.261
|View full text |Cite
|
Sign up to set email alerts
|

A Cluster Analysis Approach To Classifying Irish Native Woodlands

Abstract: The National Survey of Native Woodlands in Ireland, which was initiated in 2003, will provide two key resources identified in the National Biodiversity Plan: an inventory of native woodlands and a woodland classification system. The project has taken advantage of recent advances in GIS and remote sensing to develop a GIS-based inventory of potentially native woodland sites. Field survey and characterisation of a large subset of these sites is currently ongoing. In this paper, a proposed methodology is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Using a vegetation data set from western Montana, USA, McCune and Grace (2002) reported that a mean P-value criterion for indicator species optimized at four groups, whereas the number of significant indicators was high between three and eight groups and was zero after 12 groups. These studies, combined with others (e.g., Perrin et al, 2006), suggest that there can be considerable variability in the results of this technique among communities, which have seldom included desert vegetation, but communities at intermediate hierarchical levels are typically best discriminated through ISA. Similarly, hierarchical ISA can help identify species distribution patterns among communities at different levels of a hierarchy (Dufrêne and Legendre, 1997).…”
Section: Introductionmentioning
confidence: 95%
“…Using a vegetation data set from western Montana, USA, McCune and Grace (2002) reported that a mean P-value criterion for indicator species optimized at four groups, whereas the number of significant indicators was high between three and eight groups and was zero after 12 groups. These studies, combined with others (e.g., Perrin et al, 2006), suggest that there can be considerable variability in the results of this technique among communities, which have seldom included desert vegetation, but communities at intermediate hierarchical levels are typically best discriminated through ISA. Similarly, hierarchical ISA can help identify species distribution patterns among communities at different levels of a hierarchy (Dufrêne and Legendre, 1997).…”
Section: Introductionmentioning
confidence: 95%
“…The concept of what constitutes a native species, and its resultant conservation value, has become increasingly relevant due to the recent challenges of biodiversity loss from invasive nonnative species (Simberloff et al, 2013) and the call for biodiversity inventories to inform conservation policies (Perrin et al, 2006). Pinus sylvestris L. is one of the most widely distributed tree species in the world.…”
Section: Introductionmentioning
confidence: 99%
“…There is an opportunity to realise significant economic value where concentrated strategic planting can replace the current fragmented wooded landscape with diversity and connectivity. Perrin et al (2006) ii http://ec.europa.eu/environment/nature/biodiversity/ comm2006/2020.htm iii The figure was provided by Coillte (http://www. coillte.ie/aboutcoillte/recreation) for visits to its own landholding, although this represents the bulk of accessible forest in Ireland.…”
Section: Resultsmentioning
confidence: 99%